Grain size composition of marine surface sediments of the Canadian Arctic - Camille Brice; Jean-Carlos Montero-Serrano; Richard St-Louis (PANGAEA, 2025)
Grain size were measured on 141 marine surface and terrestrial sediment samples to study modern sediment dynamics within the Canadian Arctic (CA) and to provide an assessment of metals enrichment for V, Zn, Mn and Fe. Samples were collected from different areas between Baffin Bay and Beaufort Sea during several ArcticNet expeditions (2016-2022) onboard the Canadian Coast Guard icebreaker Amundsen. The ship helicopter was used to access terrestrial sampling sites. The marine sediments were sampled with a box corer (50cm x 50cm x 60cm) and the surface uppermost 1 cm of each box core was sampled. Push cores (10 cm diameter) were taken from each box core collected and the base (lowermost 1-2 cm) of 37 of these push cores were used in this study to establish a regional background. Grain size data were measured with a Malvern PANalytical Mastersizer 3000 laser diffraction grain-size analyzer.